PENGARUH BIAYA SOSIAL DAN INDIVIDU TERHADAP PENYELENGGARAAN PEMBELAJARAN DAN MUTU AKADEMIK SMA NEGERI DI DAERAH PERKOTAAN PROVINSI SUMATERA BARAT - Efni Cerya; Agus Irianto (Program Magister Pendidikan Ekonomi (S2), 2014)
This study aimed to measure the influence of social and private cost to learning implementation cost and academic quality of States High School in urban area of West Sumatera province. The population of this study are state high schools in urban areas of West Sumatra. Samples were purposive sampling reduced it to be 32 schools with criteria that had the national exams score for one year and financing by social and individual. The research proved that private and learning implementation cost influence on the academic quality with 0,64 determinant, but social costs are not. This study suggests to use the private cost as one input to improve the quality of academic. Keyword: social cost,private cost,learning implementation cost, academic quality